Online Activism and Connective Mourning: An Examination of the #EndSARSMemorial Protests in Nigeria - Uwalaka, Temple; Joe, Sarah; Amadi, Fred A.; Amadi, Confidence Chinedu (The Journal of communication inquiry, 2025)
This study explores how Nigerians used social media platforms to mourn and memorialize protesters who were killed during the 2020 EndSARS protests in Nigeria. Data for this study are from tweets (N = 67,678) that were scraped from the hashtags, “#EndSARSMemorial2” and “LekkiMassacre” and online semi-structured interviews (N = 30) with digital activists in Nigeria. Results show that the most frequently tweeted words were “rest in peace,” “heroes,” “who gave the order,” and “#EndSARSMemorial2.” Five themes emerged from the interview data, and they include anger and sympathy, mourning and remembering, connecting in the shared humanity of the deceased, and pledges to be better humans and citizens. The paper shows that high centrality, high density of reciprocity, and low modularity illustrate online mourners’ ability to stimulate commonality through decentralized and loose networks that allow for solidarity building during mourning and the personalization of mourning. Evoking some aspects of crisis network effects theory, this study concludes that when collective mourning occurs, individuals have more reciprocal relationships on a dyadic level and that the network has low modularity as such a network effect occurs when there is a shock that creates uncertainty in the system.